2020
DOI: 10.3390/brainsci10090623
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF’s Role as a Biomarker for Motor Training in the Context of AR-Based Rehabilitation after Ischemic Stroke

Abstract: Background: brain-derived neurotrophic factor (BDNF) may play a role during neurorehabilitation following ischemic stroke. This study aimed to elucidate the possible role of BDNF during early recovery from ischemic stroke assisted by motor training. Methods: fifty patients were included after acute recovery from ischemic stroke: 21 first received classical rehabilitation followed by ‘motor rehabilitation using motion sensors and augmented reality’ (AR-rehabilitation), 14 only received AR-rehabilitation, and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 83 publications
(86 reference statements)
0
20
0
1
Order By: Relevance
“…[35] BDNF Useful post-stroke recovery marker due to its broad neurotrophic activity and changes in its plasma concentration during recovery. [46,47,54,55] The level of BDNF does not differ between sex, age and the initial severity of stroke. [55] The correlation between low serum BDNF levels in the first day after stroke correlates with the poorer long-term functional prognosis.…”
Section: Ang2mentioning
confidence: 96%
See 3 more Smart Citations
“…[35] BDNF Useful post-stroke recovery marker due to its broad neurotrophic activity and changes in its plasma concentration during recovery. [46,47,54,55] The level of BDNF does not differ between sex, age and the initial severity of stroke. [55] The correlation between low serum BDNF levels in the first day after stroke correlates with the poorer long-term functional prognosis.…”
Section: Ang2mentioning
confidence: 96%
“…[46,47,54,55] The level of BDNF does not differ between sex, age and the initial severity of stroke. [55] The correlation between low serum BDNF levels in the first day after stroke correlates with the poorer long-term functional prognosis. [50][51][52] The positive correlation between serum BDNF level with function and mental status in post-stroke patients.…”
Section: Ang2mentioning
confidence: 96%
See 2 more Smart Citations
“…An integrative review has reported lower BDNF levels in patients with stroke [ 49 ]; in one data-driven study, stroke patients with low levels of serum BDNF had significantly higher prevalence of cognitive dysfunction than healthy controls. Another study found that BDNF levels increased during motor rehabilitation following ischemic stroke [ 50 ]. A randomised controlled trial (RCT) in Taiwan compared the effect of high-intensity interval training (HIIT) and moderate-intensity continuous training on serum BDNF and other outcomes in stroke patients.…”
Section: What Are the Potential Underlying Biological Mechanisms Imentioning
confidence: 99%